Strength of belief: Religious commitment, knowledge, and HPV vaccination adherence. Issue 6 (24th April 2019) - Birmingham, Wendy C.; Macintosh, Janelle L.B.; Vaughn, Allison A.; Graff, Tyler C.
Abstract: Objective: Human papillomavirus (HPV) infects millions of men and women annually and is a substantial contributing factor in many cancers including oral, penile, anal, and cervical. Vaccination can reduce risk but adherence nationwide and, particularly in highly religious states, is suboptimal. Religious principles of abstinence before marriage and total fidelity following marriage may create a belief of protection through adherence to religious guidelines. However, while one partner may remain monogamous, one cannot be assured of their partner's behavior both before and after marriage. These misconceptions may create a barrier to religious youth's adherence to vaccine recommendations. Methods: We sampled single young adults, age 18 to 25 years, from a Christian university classified as highly religious and a university not categorized as highly religious. Results: Highly religious young adults demonstrated low knowledge of HPV and HPV vaccination. High religious beliefs were associated with lower HPV vaccination adherence. Conclusions: Understanding the role religious beliefs have on vaccine adherence can help in the creation of campaigns that specifically address these issues. Campaigns to increase vaccination should address misconceptions of religious youth's feelings of imperviousness to sexually transmitted diseases.